Twin Rooms – new experimental test cells for testing advanced facade elements - Boris Bielek; Daniel Szabó; Josip Klem; Kristína Kaniková; Alžbeta Danková (Acta Polytechnica CTU Proceedings, 2022)
Nowadays the global trend is the integration of new materials, constructions and technological principles, which are simultaneously implemented in individual scientific and engineering disciplines. Reducing the energy intensity of buildings will increasingly resonate in individual political and professional circles. As a result, new fragments of building envelopes in the field of facade engineering are being developed and tested. Testing of building envelope is carried out either in static (laboratory) boundary conditions or in dynamic (climatic, real) conditions. The determination of the test method is conditioned by the specific intention or the investigated phenomenon within the construction of the building envelope. Currently, we finished the development and realization of the new experimental facility Twin Rooms for testing advanced elements of building envelopes in dynamic boundary conditions (in the real climate of Central Europe - Bratislava) in terms of building thermal engineering and energy efficiency of buildings. It is based on the concept of pavilion measurement. The essence of the research is that the outdoor climate is modelled by the conditions of the real outdoor climate. Test cells consists of a solar laboratory - two-room for a comparative study of the effect of solar radiation and heat transfer on energy consumption and indoor climate. The space of two identical laboratory rooms is situated inside a container - a pavilion, whose climate is a compensating space. Only the tested facade element walls are exposed to the outdoor climate. The exchange of energy with the environment is possible only through this measured facade wall. The article brings a detailed description of this experimental equipment, basic technical parameters of its technological circuits and methodology of experimental measurements.